IMPLEMENTASI SISTEM INFORMASI DI PONDOK PESANTREN DARUL KHAIRAT SUNGAI JAWI PONTIANAK - Nazilah Nazilah; Sekar Apriliza; Dita Nurfadhilah; Putri Putri; Azzara Azzara (Program Studi Manajemen Dakwah, FUAD, IAIN Pontianak, 2025)
Information system implementation has become an essential component of digital transformation in Islamic boarding school education, particularly in strengthening institutional governance and communication. This study aims to analyze how information systems and digital media management contribute to governance practices within an Islamic boarding school environment. Employing a qualitative descriptive approach, the research gathers data through direct observation, semi-structured interviews with administrators and media teams, and analysis of institutional documents and digital platforms. The findings indicate that the media division plays a strategic role in managing institutional communication, disseminating information, and documenting activities through platforms such as Instagram, Facebook, YouTube, and WhatsApp Groups, supported by the use of EMIS for educational administration. Nevertheless, implementation is constrained by unstable internet connectivity, electricity interruptions, and limited human resources in content production, including graphic design and video editing.To address these issues, the institution conducts quarterly evaluations, applies structured verification procedures for information dissemination, and develops long-term strategies such as establishing media training classes and designing integrated systems for attendance, payment, and permission processes. The implications of this study highlight the need for capacity-building in digital literacy, technological infrastructure improvement, and the formulation of standardized information governance policies to enhance institutional effectiveness. The novelty of this research lies in its comprehensive, process-oriented model that integrates administrative systems, digital media workflows, and verification-based governancean approach that fills a gap in previous studies that focused only on system development or communication outcomes. This study concludes that well-managed information systems significantly improve transparency, accountability, and institutional governance, thereby supporting the sustainable digital transformation of Islamic boarding schools. Keywords: Information Systems, Digital Transformation, Islamic Boarding School, Digital Media